Between embroidery and writing, the elaboration of the textual. The case of Embroidering for peace - Escutia Girón, Omar (2022)
This article reflects on the "Bordando por la paz" movement, which was conceived as a response to the context of violence that erupted in Mexico during the six-year term of Felipe Calderón Hinojosa. The relationship between the text, the embroidery and the gender implications is investigated, to outline the experience that takes place there. In addition, the authors seek to show embroidery as an act of collective resistance that, through the production of embroidered texts, finds a way to condolerse (commiserate) and to put in the public space the names and stories of the disappeared and murdered people in the country.